1983
DOI: 10.1148/radiology.146.2.6687370
|View full text |Cite
|
Sign up to set email alerts
|

Lateral C1-2 puncture for cervical myelography. Part III: Historical, anatomic, and technical considerations.

Abstract: Three significantly different lateral approaches to the cervical subarachnoid space (anterior, midplane, and posterior needle positions) have been previously described for cordotomy and myelography. Experimental lateral C1-2 punctures were performed by each of these three methods in anatomic specimens, cadaver models with reconstituted cerebrospinal fluid pressures, a patient with cerebral death, and to a limited degree in patients undergoing routine cervical myelography. In the cervical region the dura is pus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…13 This procedure is safe but occasionally "electrical feeling" caused by penetration of spinal needle into spinal cord was noticed, but without complications 14 . Spinal anesthesia, administered by lateral approach in sitting position of patient at the level of T10 is always associated with possibilities of potential dangers of neural damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This procedure is safe but occasionally "electrical feeling" caused by penetration of spinal needle into spinal cord was noticed, but without complications 14 . Spinal anesthesia, administered by lateral approach in sitting position of patient at the level of T10 is always associated with possibilities of potential dangers of neural damage.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,25 The absence of neurological sequelae caused by thoracic epidural procedure is supported by other studies. 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…He dissected over 20 cadavers in the School of Medicine, describing the vertebral column [12] anatomical concepts that remain up to date in what it concerns the cadaver. Still in the cadaver he observed that the dura-mater was pushed forward by the needle producing a tent, and that stall protect the spinal pia mater during spinal puncture preventing spinal cord injury [13]. The tent of the dura-mater and the risk of lesion are greater with the 18-G than with the 22-G [13].…”
Section: Cadaver Anatomymentioning
confidence: 99%
“…For intractable lower extremity pain, the needle is directed 1-2 mm anterior to the ligament to target the dorsolateral portion, whereas for upper extremity pain, the needle is directed 2-3 mm anterior to the ligament to target the ventromedial portion (Fig 1). After the outer needle has penetrated the tented dura, 18 the stylet is exchanged for the inner electrode (Cosman Medical, Burlington, Massachusetts), which has demarcations to precisely control electrode extension beyond the needle. Electrical impedance measurements from the electrode tip provide real-time feedback of anatomic location.…”
Section: Ct-guided Cordotomymentioning
confidence: 99%